2016
DOI: 10.1093/carcin/bgw073
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation in mature microRNA-608 and benefit from neo-adjuvant treatment in locally advanced rectal cancer patients

Abstract: SummaryAnalysis of a polymorphism in mature microRNA-608 (rs4919510) in rectal cancer patients enrolled in a randomized phase II clinical trial identified patient subpopulations who might benefit from the use of an intensified neo-adjuvant treatment strategy with Cetuximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…More and more studies have provided evidences to demonstrate that the SNPs in the miRNA genes, through impacting the interaction of miRNA with target genes and/or affecting the expression level of mature miRNA, result in dysregulation of target gene and consequent individual drug response and toxicity [ 9 ]. Several studies have shown that the miRNA-related SNPs are related to the efficacy and/or occurrence of adverse events of capecitabine-based chemotherapy for CRC patients [ 10 , 11 ]. For instance, Sclafani et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more studies have provided evidences to demonstrate that the SNPs in the miRNA genes, through impacting the interaction of miRNA with target genes and/or affecting the expression level of mature miRNA, result in dysregulation of target gene and consequent individual drug response and toxicity [ 9 ]. Several studies have shown that the miRNA-related SNPs are related to the efficacy and/or occurrence of adverse events of capecitabine-based chemotherapy for CRC patients [ 10 , 11 ]. For instance, Sclafani et al .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sclafani et al . have shown that the rs4919510 CC genotype in miR-608 is associated with worse outcome in rectal cancer patients treated with neoadjuvant systemic chemotherapy followed by surgery and adjuvant chemotherapy [ 10 ]. Meulendijks et al .…”
Section: Introductionmentioning
confidence: 99%
“…As consequence, a total of 35 SNPs were selected for genotyping. Although it has reported that some SNPs might affect chemotherapy efficacy in cancer patients, the evidence is not sufficient to address the role of these SNPs in survival, if only chemotherapy‐treated patients were included, unless these SNPs are also indeed involved in chemotherapy efficacy. Therefore, we first compared associations of the SNPs with survival between chemotherapy‐treated and untreated patients.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies focused on the involvement of miR-SNPs in LARC [ 121 , 122 , 123 ]. For instance, the prognostic role of the SNP rs4919510, that is characterized by the guanine to cytosine (G > C) base substitution in the sequence of the mature miRNA-608, has been explored in LARC patients subjected to neodjuvant capecitabine and oxaliplatin (CAPOX) treatment followed by CRT, surgery, or to adjuvant CAPOX ± cetuximab treatment [ 121 ]. This retrospective study showed that the CC genotype was associated with a worse 5-year progression-free survival (PFS) in LARC patients treated with chemotherapy with respect to the CG/GG genotype patients.…”
Section: Single Nucleotide Polymorphisms (Snps) At Mirnas In Larcmentioning
confidence: 99%
“…This retrospective study showed that the CC genotype was associated with a worse 5-year progression-free survival (PFS) in LARC patients treated with chemotherapy with respect to the CG/GG genotype patients. Furthermore, the administration of cetuximab to the chemotherapy and CRT, significantly improves the 5-year PFS and OS in CC carriers when compared to CG/GG genotypes [ 121 ]. This study evidenced not only the role of miR-SNPs in the risk of cancer, but also their impact in drug response.…”
Section: Single Nucleotide Polymorphisms (Snps) At Mirnas In Larcmentioning
confidence: 99%